Impact of Physiotherapy on Shoulder Kinematics in Swimmers with Swimmer’s Shoulder Pain - Alessandra Raffini; Miriam Martini; Laura Mazzari; Alex Buoite Stella; Manuela Deodato; Luigi Murena; Agostino Accardo (Sensors, 2024)
Swimmer’s shoulder is a common condition among elite swimmers, often leading to pain and reduced performance. Fatigue can exacerbate this condition by affecting shoulder strength, proprioception, and range of motion, potentially increasing the risk of overuse injuries. This preliminary study aimed to evaluate the impact of physiotherapy treatment and the effects of fatigue on shoulder kinematics using inertial and magnetic measurement units (IMUs). Five male swimmers (aged 21–27) with at least 3 years of training and suffering from swimmer’s shoulder pain participated in the study. The protocol included three sessions: dry front crawl exercises using one arm in the first and third sessions, and a fatiguing swimming exercise in the second. IMUs were used to capture 3D rotation angles, focusing on flexion/extension, abduction/adduction, and internal/external rotations during the first and third sessions. Stroke amplitude was analyzed before and after the physiotherapy treatment and fatiguing exercise. The results showed a significant increase in internal/external rotation amplitude post-fatigue before physiotherapy (p = 0.03), with a non-significant decrease in flexion/extension after treatment, suggesting improved shoulder stabilization. Despite these preliminary findings being based on a reduced number of participants, they indicate that physiotherapy may enhance shoulder motion control in swimmers with shoulder pain. Nevertheless, further studies with larger cohorts are needed to confirm these results.